Profile of Students' Misconceptions on Substance Pressure Using a Three-tier Diagnostic Test - Oktavia Damayanti Aji Putri; Tjipto Prastowo; I Gusti Made Sanjaya (IJORER : International Journal of Recent Educational Research, 2023)
Research aims to find out misconceptions experienced by students on the subject matter of substance pressure. This type of research is quantitative descriptive research using a survey method. The instrumental test used was a three-tier diagnostic test to determine the under-examined misconceptions. The research sample consisted of 43 junior high school students who had previously received substance-pressure learning materials in class. The data were analyzed by categorizing them into understanding the concept, needing more knowledge, errors, and misconception. The results of the study were as follows: (1) 9% of the students understood the concept, 51% of the students had a misconception, 34% of the students were lack of knowledge, and 6% of the students had some errors (2) misconceptions with the highest percentage were in the sub-concept of pressure gases with an average percentage of 70%, then the pressure of liquids (capillarity and osmosis in plant stems) was 52%, the pressure of solids was 51%.